Full-Crown Versus Endocrown Approach: A 3D-Analysis of Both Restorations and the Effect of Ferrule and Restoration Material - Tribst, João Paulo Mendes [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; de Jager, Niek; Bottino, Marco Antonio [UNESP]; de Kok, Paul; Kleverlaan, Cornelis Johannes (Wiley, 2020)
Purpose: To assess stress distribution in full-crowns with a composite buildup and endocrowns under axial or oblique loads, both with different ferrules (1 or 2 mm) and ceramic materials (glass ceramic or hybrid ceramic). Materials and Methods: Sixteen models were analyzed with finite element analysis. No-separation contacts were considered between restoration/resin cement and resin cement/tooth. The contact between the fixation cylinder and the root was considered perfectly bonded. The axial load was applied to the occlusal surface and the oblique load was applied to the buccal cusp. The resulting tensile stresses were shown for the crown, the cement layer and the tooth. Results: Almost all factors influenced the stress distribution significantly in the crown and the cement layer, as well as the tooth. The only exception was found under oblique loading by the restoration material and the type of crown that were of no significant influence on the stress distribution in the tooth. Conclusions: Under axial load, the endocrown showed the least tensile stresses in the tooth, but under oblique loads, the full-crown showed less tensile stresses than the endocrown. With the hybrid ceramic material, lower stresses were found in the crown, but higher stresses were present in the cement layer. The 2 mm ferrule is beneficial for reducing the resulting tensile stresses in all modalities.
Keywords: CAD/CAM; endocrown; endodontically treated teeth; finite element analysis; mandibular molar; preparation features